PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR FISIKA - I WAYAN SUINDHIA (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2023)
Learning outcomes are the output of the teaching and learning process. One of the problems in learning in schools is the low learning outcomes of students. This can be known from the initial data of students' daily test scores that are still under the Minimum Completeness Creteria (KKM). Many factors affect learning outcomes, one of which is the learning model. The Problem Based Learning Model is a cooperative learning model that requires students to be active and motivate students to support and help each other in mastering the subject matter studied. The learning model is one of the factors that affect student learning outcomes . This best practice research aims to determine the effect of the application of the Problem Based Learning model on the physics learning outcomes of grade XII MIPA1 students of SMA Negeri 1 Petang, semester 1 of the 2022/2023 academic year. In this study, it was obtained that there was an influence on student learning outcomes after applying the Problem Based Learning model. Byapplying Problem Based Learning, physics learning outcomes increased from an average completeness of 72.5% to 85.3%. ABSTRAKHasil belajar merupakan merupakan output dari proses belajar mengajar. Salah satu masalah dalam pembelajaran di sekolah adalah rendahnya hasil belajar siswa. Hal ini dapat diketahui dari data awal nilai ulangan harian siswa yang masih berada di bawah Kreteria Ketuntasan Minimal (KKM). Banyak faktor-faktor yang mempengaruhi hasil belajar salah satunya adalah model pembelajaran. Model Pembelajaran Problem Based Learning (PBL) merupakan model pembelajaran kooperatif yang menuntut siswa untuk aktif dan memotivasi siswa supaya dapat saling mendukung dan membantu satu sama lain dalam menguasi materi pelajaran yang dipelajari. Model pembelajaran adalah salah satu faktor yang mempengaruhi hasil belajar siswa. Penelitian best praktice ini bertujuan untuk mengetahui pengaruh penerapan model pembelajaran Problem Based Learning (PBL) terhadap hasil belajar fisika siswa kelas XII MIPA1 SMA Negeri 1 Petang, semester 1 tahun pelajaran 2022/2023. Dalam penelitian ini diperoleh bahwa ada pengaruh hasil belajar siswa stelah menerapkan model pembelajaran Problem Based Learning. Dengan menerapkan pembelajaran Problem Based Learning hasil belajar fisika meningkat dari rata-rata ketuntasan 72,5% menjadi 85,3%.